FINANCIAL SUPPORT OF AGRICULTURAL PRODUCERS - Levandivskyi, O.T.; Yurchilo , I.Y. (The actual problems of regional economy development, 2021)
The article analyzes the current state, development trends and features of financial security of agricultural producers. It is proved that the agricultural sector of Ukraine is characterized by constant dynamics, which leads to a change in trends in the financial support of agricultural activities. The financial support of agricultural enterprises through bank lending programs is considered. The main problems faced by the participants of the market of financial support of agricultural producers are revealed. The problems of crediting and risks in the financial and agricultural sectors of the economy are studied. Statistical data of 2014 - 2020 were used. When analyzing the dynamics of lending to agricultural producers, it was found that the share of long-term loans is only 5%. Based on the analysis of interest rates on credit resources and profitability of agricultural enterprises, it is established that when the level of profitability is higher than the average annual interest rates on loans, it is advisable to reinvest profits of agricultural producers in their own activities, which will positively affect their further development. It is studied that despite the state support of agricultural producers, their level remains low compared to other countries. The interaction of financial institutions and the agricultural sector through the mechanism of state support has been established. The formulated methodology of relations makes it possible to develop a set of measures for active cooperation between the financial and agricultural sectors of the economy. Such measures include diagnosing the financial condition of agricultural enterprises, which will reduce the risk of non-refund. Also, the expansion of financial support for agricultural producers with the involvement of programs of their state support can be carried out by: lowering interest rates on loans; increase in government allocations for cheaper loans; increase in lending to small and medium-sized agricultural enterprises, etc. All these actions will provide an opportunity to stimulate the development of agricultural producers and create a favorable climate for investing in the agricultural sector of the economy.